2004
DOI: 10.2320/matertrans.45.793
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reduction Capability of Resin Material on the Solder Wettability for Electrically Conductive Adhesives (ECAs) Assembly

Abstract: Electrically conductive adhesives (ECAs) have been developed as an alternative to traditional Sn-Pb solders for electronic and optoelectronic applications. However, there are critical limitations such as the low conductivity, and unstable contact resistance. These limitations have seriously hindered the broad applications of ECAs. In order to overcome these limitations, a new formulation using Pb-free conducting filler particles was proposed. Our previous study proved that the metallurgical interconnections am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Otherwise, the flow-coalescence-wetting behavior of LMPA fillers in the ICA during the adhesive bonding process is hindered by excessive curing of the ICA. 11,12) As shown in the results, the polymer matrix does not excessively. In addition, the polymer matrix was maintained at a sufficiently low viscosity for the molten LMPA fillers to flow, coalesce with each other, and wet the upper and lower electrodes.…”
Section: Methodssupporting
confidence: 49%
“…Otherwise, the flow-coalescence-wetting behavior of LMPA fillers in the ICA during the adhesive bonding process is hindered by excessive curing of the ICA. 11,12) As shown in the results, the polymer matrix does not excessively. In addition, the polymer matrix was maintained at a sufficiently low viscosity for the molten LMPA fillers to flow, coalesce with each other, and wet the upper and lower electrodes.…”
Section: Methodssupporting
confidence: 49%
“…After the upper test board was mounted and the assembly was reflowed, the fillers almost coalesced and wet on the copper patterns. In our previous work, 13 we demonstrated that one of the obstacles to this coalescence and wetting process was the oxide-film present on the surfaces of both the copper wiring and the fillers. As for the ECA formulation without reduction capability, the Sn-In solder alloy did not wet and the wetting angle on the copper surface was about 156.8°.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies [10][11][12] have shown that using fluxing capability to remove oxides of both LMPA fillers and conduction pads helps to promote wetting characteristics. The polymer should not be cured too much before it reaches the melting point of the LMPA filler in order to achieve a good electrical conduction path.…”
Section: Self-organized Interconnection Process Using Solderable Acamentioning
confidence: 99%